INTERVENSI PEKERJA SOSIAL GENERALIS TERADAP KLIEN ANAK : Pekerja Sosial Perlindungan Anak Kementerian Sosial RI di D.I. Yogyakarta - Idan Ramdani (WELFARE : Jurnal Ilmu Kesejahteraan Sosial, 2020)
This article is the result of a study describing the generalist social worker intervention on clients under 18 years of age, by the Indonesian Ministry of Social Services child social service voluntary service unit in the Special Region of Yogyakarta. This study uses a qualitative descriptive research type, with a case study approach that seeks to understand deeply related to the intervention of generalist social workers. The results of this study indicate that the interventions carried out are based on Permensos No. 22 of 2014 which refers to several stages, namely: Initial assessment, disclosure of problems, preparation of intervention plans, problem-solving, resocialization, termination and the last is advanced guidance.Keywords: Intervention, Generalist Social Worker, Child Protection Social Work Unit.